Affirmative action and university fit: Evidence from Proposition 209 - Peter Arcidiacono; Esteban Aucejo; Patrick Coate; V. Joseph Hotz (IZA Journal of Labor Economics, 2014)
Proposition 209 banned the use of racial preferences in admissions at public colleges in California. We analyze unique data for all applicants and enrollees within the University of California (UC) system before and after Prop 209. After Prop 209, minority graduation rates increased by 4.35 percentage points. We present evidence that certain institutions are better at graduating more-prepared students while other institutions are better at graduating less-prepared students and that these matching effects are particularly important for the bottom tail of the qualification distribution. We find that Prop 209 led to a more efficient sorting of minority students, explaining 18% of the graduation rate increase in our preferred specification. Further, there appears to have been behavioral responses to Prop 209, by universities and/or students, that explain between 23% and 64% of the graduation rate increase.
Keywords: I28; J15; 330; Affirmative action; College enrollment; College graduation; Mismatch; Ethnische Diskriminierung; Antidiskriminierungsrecht; Hochschule; Schulbesuch; Bildungsabschluss; Bildungsniveau; Bildungsertrag; Kalifornien; USA